Stimulating Plant Growth with Microorganisms and Hormones in Worm Compost - Fitri Anugrah Sari (Newinera Publisher, 2021)
Worm compost is a fungus that carries microorganisms and hormones that stimulate plant growth. Because of the vast number of microorganisms present and their high activity, the transfer of nutrients from worm droppings into forms that are accessible to plants may be accelerated. For decorative plants, vegetables, and fruits, the purpose of this research is to investigate the rise in plant growth on both a vegetative and generative level. Excellent for use as a planting medium combination in nurseries due to its high porosity. Containing hormones that have the potential to enhance the soil's physical, chemical, and biological qualities.